2011
DOI: 10.1038/hdy.2011.85
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insights into adaptation to high-altitude environments

Abstract: Elucidating the molecular genetic basis of adaptive traits is a central goal of evolutionary genetics. The cold, hypoxic conditions of high-altitude habitats impose severe metabolic demands on endothermic vertebrates, and understanding how high-altitude endotherms cope with the combined effects of hypoxia and cold can provide important insights into the process of adaptive evolution. The physiological responses to high-altitude stress have been the subject of over a century of research, and recent advances in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
120
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 116 publications
4
120
0
1
Order By: Relevance
“…Finally, interleukin 21 signaling has a critical role in promoting the lung inflammatory response to acute pneumovirus infection (Spolski et al, 2012). Adaptation to altitude has received attention in humans (see Cheviron and Brumfield, 2012 for a review), and physiological differences caused by altitude have been studied in cattle (Wuletaw et al, 2011). However, to our knowledge, this is the first report of indirect evidence of genetic adaptation to altitude in livestock.…”
Section: Discussionmentioning
confidence: 56%
“…Finally, interleukin 21 signaling has a critical role in promoting the lung inflammatory response to acute pneumovirus infection (Spolski et al, 2012). Adaptation to altitude has received attention in humans (see Cheviron and Brumfield, 2012 for a review), and physiological differences caused by altitude have been studied in cattle (Wuletaw et al, 2011). However, to our knowledge, this is the first report of indirect evidence of genetic adaptation to altitude in livestock.…”
Section: Discussionmentioning
confidence: 56%
“…This reversible modification of complex physiological traits can be driven by changes in the regulation of genes at several levels of hierarchical organization (Cheviron and Brumfield, 2012). Our acclimation treatments successfully altered junco thermogenic performance, and we found that changes in performance were associated with underlying transcriptomic changes in interacting hierarchical pathways.…”
Section: Discussionmentioning
confidence: 76%
“…For instance, deer mice (Peromyscus maniculatus) living at high altitude exhibit greater thermogenic capacities compared with their lowland counterparts, and this enhanced performance has been linked to regulatory changes in the expression of genes that influence the use of metabolic fuel and oxygen (Cheviron et al, , 2014. Because changes in gene regulation allow the genome to rapidly and reversibly respond to environmental variation, transcriptomic studies can provide key insights into the mechanistic underpinnings of phenotypic flexibility and the adaptive modification of complex physiological traits, both of which require concerted changes in hierarchical and interacting regulatory networks (Cheviron and Brumfield, 2012). The hierarchical nature of complex physiological traits is well illustrated by the following three levels of physiological adjustment that enhance aerobic thermogenic performance (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Physiological studies have shown that Andeans and Tibetans are different at high altitude with Tibetans being more adapted to high altitude with attributes more similar to sealevel populations [84]. Genetic studies have shown that differences in the genetics between Andean and Tibetans resulted in convergent phenotypic evolution between high and low altitude populations [85,88,89]. Recently, a genome-wide study compared two populations native to high altitude for several millennia: (i) the native inhabitants of the Tibetan Plateau and (ii) the native inhabitants of the Andean Altiplano of South America.…”
Section: Natural Human Models For Studying Placental Dysfunctionmentioning
confidence: 99%